2016
DOI: 10.1097/npt.0000000000000133
|View full text |Cite
|
Sign up to set email alerts
|

Using the TIDieR Checklist to Standardize the Description of a Functional Strength Training Intervention for the Upper Limb After Stroke

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 40 publications
0
18
0
4
Order By: Relevance
“…Functional strength training for the upper limb after stroke combines strength training of weaker muscles with task-specific training through “repetitive, progressive, resistance exercise during goal-directed functional activity” ( 53 ). Research therapists provided external feedback and verbal prompting whilst only using hands-on contact for safety (“therapist-independent”).…”
Section: Methodsmentioning
confidence: 99%
“…Functional strength training for the upper limb after stroke combines strength training of weaker muscles with task-specific training through “repetitive, progressive, resistance exercise during goal-directed functional activity” ( 53 ). Research therapists provided external feedback and verbal prompting whilst only using hands-on contact for safety (“therapist-independent”).…”
Section: Methodsmentioning
confidence: 99%
“…The final core intervention content is described below in the following sections and has been designed equally acknowledging the importance of applying appropriate theoretical frameworks as well as user feedback. For further details on the intervention see Additional file 4 where the Template for Intervention Description and Replication (TIDieR) checklist is reported to ensure the completeness of reporting, and ultimately the replicability, of interventions [40]. For further details on validated tools/questionnaires used within the intervention please see the PATHway RCT protocol [41].…”
Section: Final Intervention Structure and Content Resulting From The mentioning
confidence: 99%
“…The feasibility of the TIDieR checklist in systematically describing physical therapy interventions is only currently being explored. 22 van Vliet et al 22 identified few items in the TIDieR checklist as unclear and overlapping based on their recent study, which evaluated the TIDieR checklist to describe a therapy intervention used in the stroke rehabilitation trial.…”
Section: Methodsmentioning
confidence: 99%